A REVIEW ON SOIL CONTAMINATION SOURCES: IMPACT ON ENGINEERING PROPERTIES AND REMEDIATION TECHNIQUES - Sahar AL-khyat; Dalia Naji; Huda T. Hamad; Helen Onyeaka (Journal of Engineering and Sustainable Development, 2023)
Soil contamination produced by improper management of various petroleum and industrial products causes potential risks to the environment and soil engineering properties. Such contamination causes environmental deterioration and adversely affects soil engineering performance, altering almost all geotechnical properties. Several remediation techniques have been proposed to decontaminate the polluted soils. Choosing the best technique depends on both the energy consumption during operation and the treatment efficiency. The lack of a universally appropriate treatment method and the unavoidable expansion of contaminated land have justified the sake of reviewing the behavior of contaminated soils to develop both environmentally and geotechnically suitable soils for construction projects. The present paper reviewed some soil contamination sources’ backgrounds, effects, and remediation methods. Soils influenced by petroleum hydrocarbons and industrial effluents were evaluated. According to the reviewed studies, contaminants are evidenced to have a negative impact on soils' geotechnical characteristics by increasing settlement and swelling, reducing shear strength, and decreasing permeability. The need to restore the engineering characteristics of soils suggest the necessity to use remediation or stabilization technique. The electrochemical method, bioremediation, and stabilizing by additives are revealed to be efficient in improving the engineering properties and performance of contaminated soils.